PERANAN TAN THIAM KWIE DALAM PENDIDIKAN MUSIK BARAT DI INDONESIA - Surtihadi, R.M. (Acintya, 2009)
What I would like to write down here is an article which strong focuses on Tan Thiam Kwie as a maestro music education. This article originally is a research based on Tan Thiam Kwie as a person who dedicated to his life in the field of music education. This article use a historical method especially in addition by using oral history method and its relation with local history perspectives. Because of the concentration range proposed to be his musical life and his dedication to the Western Music education in Indonesia, so that the article connected to the examination of Western music education and its education institutionally establised throuugh the founding of the Sekolah Musik Indonesia (SMIND) and Akademi Musik Indonesia (AM!) on 1952 in Yogyakarta. There is a logic reason when Mr. Tan as a one of founder this music education institutionally connected to his loyality and his dedication to his own life.Â Keywords: local history, a maestro, music education.